The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/w8100420
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Climate Change Impacts on Water Resources in the Songhua River Basin

Abstract: Abstract:The Songhua River Basin (SRB) in Northeast China is one of the areas most sensitive to global climate change because of its high-latitude location. In this study, we conducted a modeling assessment on the potential change of water resources in this region for the coming three decades using the Soil and Water Assessment Tool (SWAT). First, we calibrated and validated the model with historical streamflow records in this basin. Then, we applied the calibrated model for the period from 2020 to 2049 with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…These results can also be compared to those obtained by Estrela et al [3], who also projected a reduction in mean annual runoff for the SRB between 21% and 33%. Overall, the increase in temperature and the projected decrease in precipitation will result in increased evapotranspiration, which will interact to reduce streamflow significantly [52]. Comparing precipitation and streamflow results, it can be seen that, due to higher actual evapotranspiration, the decreases obtained in streamflow exceed those in precipitation by 20%.…”
Section: Annual Streamflow Changementioning
confidence: 99%
“…These results can also be compared to those obtained by Estrela et al [3], who also projected a reduction in mean annual runoff for the SRB between 21% and 33%. Overall, the increase in temperature and the projected decrease in precipitation will result in increased evapotranspiration, which will interact to reduce streamflow significantly [52]. Comparing precipitation and streamflow results, it can be seen that, due to higher actual evapotranspiration, the decreases obtained in streamflow exceed those in precipitation by 20%.…”
Section: Annual Streamflow Changementioning
confidence: 99%
“…The Budyko curve based on Budyko's assumption [36] is developed by two balance equations on water and energy. One is Equation (9), and the other is Equation (10), to represent the energy balance in a basin [52].…”
Section: Generation Of Simulated Runoff By Hydrological Sensitivitymentioning
confidence: 99%
“…These studies dealt with gradual and abrupt trends in precipitation, temperature and runoff, and they found that climate change by global warming was likely to increase the incidence of extreme events, causing more severe floods and droughts [5][6][7][8][9]. Labat et al [10] found evidence for a 4% increase in global runoff with each 1 K increase in mean global temperature due to climate warming.…”
Section: Introductionmentioning
confidence: 99%
“…The warm-drying trend has contributed to considerable wetland degradation and agricultural hazards in Northeast China [37]. The continue decreasing in streamflow may possess a large pressure on surface and subsurface water resources [38][39][40]. This calls for more authority basin-wide regulations to manage water resources to meet the balance among agricultural sector, ecosystem and domestic water utility.…”
Section: Discussionmentioning
confidence: 99%